Planktonic foraminifera document palaeoceanographic changes across the middle Cenomanian carbon-isotope excursion MCE 1: new evidence from the UK chalk - Petrizzo, MR; Gale, AS (Geological Magazine, 2022)
Planktonic foraminifera were studied at Lydden Spout, near Folkestone (southeast England, UK), the reference section of the middle Cenomanian Event 1 (MCE 1) characterized by a prominent double-peak delta C-13 excursion of 1 parts per thousand identified in different ocean basins and considered a global event. Biostratigraphic and quantitative analysis of planktonic foraminifera are correlated to the delta C-13 perturbation, to the positive delta O-18 shifts identified within MCE 1 and to the occurrence of Boreal macrofossils (the bivalves Chlamys arlesiensis and Oxytoma seminudum, and the belemnite Praectinocamax primus). Variations in abundance and species richness of planktonic foraminifera and the inferred palaeoecological preferences of taxa permit the identification of distinct palaeoenvironmental settings across MCE 1. The stratigraphic interval corresponding to MCE 1 is characterized by the absence of oligotrophic rotaliporids, and by the evolutionary appearance of meso-eutrophic dicarinellids and of Muricohedbergella portsdownensis, a cold-water species that occurs at the same level as the Boreal macrofossils. These observations indicate a palaeoceanographic scenario characterized by reduced stratification of surface waters and absence/disruption of the thermocline in a dominantly eutrophic regime during MCE 1. Evidence provided by planktonic foraminifera, Boreal macrofossils and delta O-18 records documented for the late Cenomanian Plenus Cold Event (PCE) at Eastbourne (UK) reveal similarities that confirm the periodic inflow of cold Boreal seawater originating in the Norwegian Sea as previously postulated to explain the occurrence of Boreal fauna in the Anglo-Paris Basin. The southerly extension of this water mass may be related to the reorganization of circulation driven by the long eccentricity cycle.